Diagnosis of bone metastasis in patients with non-small cell lung cancer by combined detection of CEA, CYFRA21-1, and ALP - Ye, Haiying; Zhang, Qiaoli (Vojnosanitetski pregled, 2025)
Background/Aim. Despite significant advances in the diagnosis and treatment of non-small cell lung cancer (NSCLC), the overall prognosis remains poor, especially when bone metastasis occurs with disease progression. The aim of this study was to examine the diagnostic value of combined detection of carcinoembryonic antigen (CEA), cytokeratin 19 fragment antigen 21-1 (CYFRA21-1), and alkaline phosphatase (ALP) for bone metastasis in NSCLC patients. Methods. In total, 148 patients with NSCLC were included in the study. They were selected from patients hospitalized for treatment between April 2020 and March 2022. Out of the total number of patients, 68 were assigned to the metastasis group and 80 to the non-metastasis group. Their blood samples were collected to measure CEA, CYFRA21-1, and ALP levels in the serum. Multivariate logistic regression analysis was conducted to determine the factors contributing to bone metastasis. Receiver operating characteristic (ROC) curves were plotted to analyze the diagnostic value. Results. Bone metastasis occurred in 68 (45.94%) patients. The baseline data exhibited no significant intergroup differences (p > 0.05). The metastasis group had significantly raised serum CEA, CYFRA21-1, and ALP levels compared to those of the non-metastasis group (p < 0.05). The increases in serum CEA [odds ratio (OR): 1.062, 95% confidence interval (CI): 1.031–1.094], CYFRA21-1 (OR: 1.155, 95% CI: 1.061–1.258), and ALP (OR: 1.027, 95% CI: 1.008–1.047) were risk factors for bone metastasis (OR > 1, p < 0.05). The areas under the ROC curves of CEA, CYFRA21-1, ALP, and their combination were all greater than 0.600, suggesting high diagnostic values. Conclusion. CEA, CYFRA21-1, and ALP levels in the serum can predict bone metastasis in NSCLC patients, and the predictive value of their combination is higher than that of any single indicator.